Oral manifestations, microbial study and salivary IgA study in asthmatic patients receiving prednisolone - Mushtaq T Ibraheem; Fawaz D Al-Aswad (College of Dentistry/ University of Baghdad, 2014)
Background: Asthma is a disease of the airways characterized by chronic inflammation associated with airway hyper-responsiveness and airway wall remodeling. Aims of the study: The aims of this study was to determine the prevalence of oral manifestations , identify different microorganism from oral micro flora and determination of salivary IgA and salivary flow rate in asthmatic patients taking different dose of Prednisolone in comparison with control group. Subjects, materials and methods: The study included 17 patients under treatment with Prednisolone (10-20 mg),15 patients take (20-30 mg) of Prednisolone and other 18 patients take (30 - 40mg) of Prednisolone, and 25 healthy control group (10 male and 15 female). Results : The most frequent oral manifestations in asthmatic patients on Prednisolone was burning mouth syndrome, then dry mouth, tooth erosion and white coated tongue and decreased in salivary flow rate. High prevalence of Staphylococcus aureus , Staphylococcus epidermidis , streptococcus Viridians and Candida albicans in patients with asthma and difference in oral microbial isolation between asthmatic patients take different dose of Prednisolone and healthy control.The level of salivary IgA in asthmatic patients treated with Prednisolone less than healthy control. Conclusions: The findings of this study show an obvious difference in the prevalence of oral manifestation and some micro-organisms between patients with asthma and healthy control. Decrease of IgA and salivary flow rate in patients with asthma as compared to healthy control.